Monolingualism vs. bilingualism: Formants as a personal identification of Slovenian and Italian vowels – absolute values versus ratios - Skubic, Darija; Ozbič, Martina (Slavia Centralis, 2025)
Since the speakers in this research differ in age, gender, emotions, physical condition, etc., the absolute values of the formants are different. Comparing the ratios between the formants shows that the values of the ratios between the formants are much more stable and comparable than the absolute values. The present paper analyses the relationships between formants F1, F2 and F3 on the basis of published formant measurements for Slovene and Italian and determines whether the relationships are constant regardless of the absolute values of the individual formants. The aim of the study was to compare the Italian and Slovenian formant relationships in monolingual and bilingual speakers. The results show, among other things, that descriptive statistical measures for stressed vowels in monolingual Italian-Slovenian speakers display a decrease in the mean value of F2/F1 from front to back vowels, with a minimum value for central and back vowels.